Effects Of Plastering And Glass Fibre Reinforced Polymer (Gfrp) On Concrete Masonry Prism Strength Capacity - Ismail, Mohammad Fikri (Universiti Sains Malaysia, 2017)
Masonry based construction has long been used in various types of structures, houses, public and private buildings and also historical monuments. The loading capacity of masonry especially for the load-bearing wall can be increased by various methods available. In order to increase the resilience of a masonry structure, methods that can be used are plastering and strengthening. In this research, four types of concrete masonry prisms have been introduced to compare its behaviour against loading. Those specimens are classified as controlled specimen without any plaster, one-sided plastered, two-sided plastered, and specimen strengthened by Glass Fibre Reinforced Polymer (GFRP) strip in a vertical orientation. Characterization tests such as absorption test and compressive strength test were conducted on concrete masonry unit (CMU) to determine its characteristics before mortar mix are applied for bonding. Compressive test and flexural test were conducted to characterize the mortar mix used. A total of 12 prisms specimens with four different conditions was produced for the compressive strength test. Each condition has a total of three specimens each to compare their outcomes. The test results showed that two-sided plaster specimen have the highest average loading capacity of 209 kN. In this study, all conditions used the same method during the production process and proved that both sides plaster can improve the ability of the masonry structure to resists high loading.